Implementation of the institutional plans in the Gauteng provincial legislature - Ngonini, Yolanda (University of the Witwatersrand, Johannesburg, 2023)
This research examined the implementation of institutional plans in the Gauteng Provincial Legislature (GPL). This research applied a qualitative design with the aid of a case study. Research respondents were chosen through a purposive selection. Semi- structured interviews were utilised in collecting data and thematic analysis is applied in the analysis of the data gathered. Institutional plan implementation was shown to be a critical part of the GPL and its effectiveness determined the extent to which the GPL could deliver its mandate as enshrined in the Constitution. The research further revealed that the plans were usually quarterly or annual, depending on the anticipated targets of the GPL. However, despite ensuring the effective implementation of the institutional plans, the research revealed that this process was undermined by several factors, chief amongst them being the inability of those in the top echelons of the GPL to include all key interested parties in the planning process. Failing to involve those with a high stake and influence in the GPL plans meant that the implementation was marred by bottlenecks. In light of these challenges, the research recommends the need to apply a multi-stakeholder approach in the planning and implementing of institutional plans in South African provincial legislatures. Effective communication was also identified as a missing link, hence there is a need to address this challenge by ensuring that implementing institutional plans within the GPL is a process that is inclusive and accommodating the needs stakeholders directly or indirectly involved
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Public Policy to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Gauteng Provincial Legislature (GPL); Constitution; UCTD; SDG-11: Sustainable cities and communities